2022
DOI: 10.3390/ijerph19073815
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Waste Separation Management Policies in the Yangtze River Delta Based on the PMC Index Model

Abstract: Numerous policies have been formulated and implemented to strengthen waste separation management activities in many countries. Waste separation management policies (WSMPs) must be evaluated as the precondition for reducing deviations from policy implementation and improving waste separation performance. Based on text mining technology and the construction of a policy modeling consistency (PMC) index model, we conducted a quantitative evaluation of 22 WSMPs issued by central governmental departments and provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Based on the PMC-index model system established by Ruiz Estrada, scholars adapted the indicator system according to their research objectives and the content and characteristics of different policies, achieving good evaluation results [58,59]. Based on the content characteristics of CSR policy and the conclusion of high-frequency word analysis, we constructed the PMC-index model variable evaluation system, as shown in Table 2.…”
Section: Establishment Of the Pmc-index Modelmentioning
confidence: 99%
“…Based on the PMC-index model system established by Ruiz Estrada, scholars adapted the indicator system according to their research objectives and the content and characteristics of different policies, achieving good evaluation results [58,59]. Based on the content characteristics of CSR policy and the conclusion of high-frequency word analysis, we constructed the PMC-index model variable evaluation system, as shown in Table 2.…”
Section: Establishment Of the Pmc-index Modelmentioning
confidence: 99%
“…Dai et al (36), based on a study on 16 green development policies concerning the Yangtze River Economic Belt, suggested five indicators, including policy timeliness, social benefits, audience scope, incentives, and constraints, significantly affected the quality of policy design. Liu and Liu (37) analyzed waste separation management policies issued by central government departments and provincial governments in the Yangtze River Delta from 2013 to 2021 and found that existing policies have great potential for optimization in terms of stricter constraint regulations, context-appropriate incentives, and the cultivation of market participants. In addition, many studies were using the PMC index model for fields, including new energy industry policy (38,39), plastic bag ban policy (40), and textile industry policy (41), as well as ecological compensation policy (42), which reflected that this evaluation tool has good applicability and effectiveness in facilitating the quantitative policy studies and opening the black box in policy design.…”
Section: Applications Of the Pmc Index Modelmentioning
confidence: 99%
“…Since the design of our evaluation indicator system included nine firstlevel indicators, the theoretical values of the calculated PMC index should be in the [0, 9] interval. Referring to the practice of previous literature (37,45) and combining the research needs of this study, we classify the measured PMC index values into six levels of consistency. Specifically, the values of the PMC index belong to the [0, 4) interval, [4,6) interval, [6,7) interval, [7,8) interval, [8,9) interval, or equal to nine, indicating that TCMDPs have "poor performance, " "acceptable performance, " "good performance, " "excellent performance, " .…”
Section: Measurement Of the Pmc Indexmentioning
confidence: 99%
“…There is a certain degree of subjectivity in the quantitative evaluation policies, while the qualitative methods are more scientific. Qualitative policy evaluation methods have been ap-plied in some fields (Dai et al 2021;Liu and Liu 2022), but lack application in the field of contract energy management. Therefore, this paper will mainly discuss the following issues: (1) Does the current energy saving subsidy policy have defects?…”
Section: Introductionmentioning
confidence: 99%